Coccinellid predators of mealybugs infesting banana in South India, including a new species and a new record of Scymnus Kugelann (Coleoptera: Coccinellidae), with notes on other natural enemies - Poorani, J.; Anuradha, C.; Thanigairaj, R.; Mol, P. Prashina (Zootaxa, 2024)
Several species of mealybugs infest various parts of bananas and plantains including foliage, fruits, rhizome and roots in all the major banana growing regions of India and cause moderate to occasionally serious damage but systematic attempts at documenting the mealybug pests of banana and their natural enemies are lacking in India. In this study, mealybugs infesting bananas and plantains in Tamil Nadu, South India, are documented along with their coccinellid predators and other natural enemies. The exotic Jack Beardsley mealybug, Pseudococcus jackbeardsleyi Gimpel & Miller, was found to be a major pest of banana bunches in all localities surveyed in Tamil Nadu and the grey pineapple mealybug, Dysmicoccus neobrevipes Beardsley, was a serious pest in some isolated pockets. Three coccinellids, Scymnus (Pullus) coccivora Ramakrishna Ayyar, Nephus regularis Sicard and Slipinskiscymnus saciformis (Motschulsky) were found to be the major predators of all species of mealybugs. Brumoides suturalis (Fabricius) was predatory on solenopsis mealybug (Phenacoccus solenopsis Tinsley) only and Hyperaspis maindroni Sicard was associated with solenopsis mealybug and pink pineapple mealybug (Dysmicoccus brevipes (Cockerell)). One new species, Scymnus (Pullus) spicatus sp. n., is described as a predator of Jack Beardsley mealybug and striped mealybug (Ferrisia virgata (Cockerell)). Scymnus (Pullus) syoitii Sasaji, 1971, a Japanese species, is recorded for the first time from India as a predator of banana root mealybugs in Tamil Nadu and on Planococcus citri (Risso) in Karnataka. Brief notes on the other natural enemies of banana mealybugs are also given with illustrations.